Synthesis of an insulin-loaded mucoadhesive nanoparticle designed for intranasal administration: focus on new diffusion media - Jamshidnejad-Tosaramandani, Tahereh; Kashanian, Soheila; Karimi, Isaac; Schiöth, Helgi B. (Frontiers in Pharmacology, 2023)
Intranasal administration is a drug delivery approach to provide a non-invasive pharmacological response in the central nervous system with relatively small peripheral side effects. To improve the residence time of intranasal drug delivery systems (DDSs) in the nasal mucosa, mucoadhesive polymers (e.g., chitosan) can be used. Here, insulin-loaded chitosan nanoparticles were synthesized and their physiochemical properties were evaluated based on requirements of intranasal administration. The nanoparticles were spherical (hydrodynamic diameter of 165.3 nm, polydispersity index of 0.24, and zeta potential of +21.6 mV) that granted mucoadhesion without any noticeable toxicity to the nasal tissue. We applied a new approach using Krebs-Henseleit buffer solution along with simulated nasal fluid in a Franz’s diffusion cell to study this intranasal drug delivery system. We used Krebs-Henseleit buffer because of its ability to supply glucose to the cells which serves as a novel ex vivo diffusion medium to maintain the viability of the tissue during the experiment. Based on diffusion rate and histopathological endpoints, Krebs-Henseleit buffer solution can be a substituent solution to the commonly used simulated nasal fluid for such DDSs.